Student Perception of “Google Translate” Application as a Media for Translating English Material at the Second Grade Students of SMAN 10 Mataram - Widya, Ni Putu Puspa Widyarni Sari; Baharuddin; Amrullah; Putera, Lalu Jaswadi (Journal of Classroom Action Research, 2025)
As technology plays an increasingly significant role in education, tools like Google Translate have become widely accessible for language learning and translation. This study investigates the perceptions of second-grade students at SMAN 10 Mataram regarding the use of the Google Translate application as a tool for translating English materials. The research employs a qualitative descriptive method. This study used structured interviews based on a set of guidelines to evaluate students' perceptions of Google Translate as a tool for translating English content. A qualitative and descriptive approach was applied for data collection, with the data presented and analyzed in stages, starting with interview analysis. The interviews, incorporating questions based on the 5W + 1H framework, aimed to gather information about students' perceptions before and after using Google Translate, as well as the challenges they faced and their strategies for overcoming them. Mobile phones and note-taking were used to record and capture additional information during the interviews. The findings show that most students view Google Translate as a helpful, time-efficient, and user-friendly tool for understanding English texts. However, limitations such as inaccuracies in grammar and context were noted. Despite these issues, most students have a positive attitude towards using Google Translate as a supplementary aid in their English learning. The study concludes that while Google Translate is a valuable resource, it should be used alongside teacher guidance and other learning strategies to enhance language proficiency.